EKSISTENSI PIDANA DENDA DALAM PROSES PERADILAN PIDANA DI INDONESIA - Yuliana, Yuliana (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT            Criminal fines for one of the main penalties determined in article 10 of the Criminal Code, in its development, the value of the amount of the penalty determined in Book II and Book III of the Criminal Code is no longer sufficient. The purpose of this consideration is to find out the existence of punishment in the Indonesian criminal law system.            This type of research is normative legal research by studying the laws and concepts of parents. Using sources of primary, secondary and non-legal legal materials. Then the legal material is processed in a deductive way and then draws more specific and complete conclusions.            The application of imprisonment in Indonesia has not been maximized. Criminal fines do not have the maximum function and role because law enforcement chose to choose jail or confinement rather than imprisonment. This relates to imprisonment up to now is still preferred in the determination and sentence in his debate with the aim of punishment, most of which require a deterrent effect to bet and try in general. In the development of a new conception in criminal law, what stands out is the development of penalties for cover for freedom of fines, more importantly for minor crimes or crimes threatened with imprisonment under one year, the application of defense in Samarinda District Court is minimal, it is believed that the dominance of imprisonment or imprisonment is still dominant as an effect on security, not to mention the factors that influence each judge's decision. Most important is the lack of the challenge of imprisonment fines which makes judges prefer jails or confinement over imprisonment fines. Keywords: Existensi, Criminal Fines, Judicial Process, Indonesia